URGENSI PEMBATASAN UMUR PERKAWINAN DALAM UNDANG-UNDANG NO 16 TAHUN 2019 TENTANG PERKAWINAN (PERSPEKTIF SADD ADZ-DZARÎ’AH) - Fadillah, Nor (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: The marriage constitution in the article 7 No 16 of 2019, “A marriage is only permitted if a man and a woman have reached the age of 19”. The age restriction in marriage is not clearly stated and determined in either Al-Qur’an or Hadis as it is stated in the constitution. So based on this issue, this research tries to examine the correlation of theory Sadd Adz-Dzari’ah on the article 16 of 2019 Marriage Age Restriction. This type of research is a normative legal research based on constitution and analytical approaches, then analyze it qualitatively. Based on the result of this research could be concluded that, the age restriction is not found technically written in the Al-Qur’an and Hadis, however it is said in the Al-Qur’an and Hadis to carry out the marriage when someone reaches the puberty and adequate enough to do so. The marriage which carried out by ignoring the age restriction will bring out some damage toward psychology, social, reproduction health, some risk at giving birth and divorce. The quality of those damages might be included as dzari’ah criteria which most likely (ghalabah dzhon) issue some harms and must be avoided is to restrict the age, age restriction is an important thing in the household life, because it’s one of the supporting factor to achieve the marriage purpose in which to build the sakinah mawaddah warahmah family.Keywords: The Correlation of Age Restriction; Marriage. Abstrak: Undang-Undang Perkawinan pada pasal 7 No 16 Tahun 2019, “Perkawinan hanya diizinkan apabila pria dan wanita sudah mencapai umur 19 tahun”. Pembatasan umur dalam perkawinan ini tidak disebutkan dan ditentukan secara jelas dalam nash, maka dari sinilah penelitian ini berangkat, yakni berusaha untuk mengkaji korelasi teori Sadd Adz-Dzari’ah terhadap Undang-Undang No 16 Tahun 2019 tentang pembatasan umur perkawinan, Jenis penelitian ini adalah hukumnormatif dengan pendekatan Undang-Undang dan analitis dan menganalisisnya secara kualitatif. Hasil dari penelitian ini yaitu pembatasan umur dalam perkawinan memang tidak ditemukan secara tertulis dalam Al-Qur’an dan Hadis, akan tetapi dalam Al-Qur’an dan hadis menyebutkan anjuran pernikahan untuk orang yang sudah baligh serta mampuuntuk menikah. Perkawinan yang dilaksanakan dengan mengabaikan pembatasan umur akan melahirkan dampak negatif yaitu dari segi psikologis, sosial, kesehatan reproduksi, resiko ketika melahirkan, dan perceraian. Kualitasdampak negatif tersebut termasuk kriteria dzari’ah yang kemungkinan besar (ghalabah dzon) akan terjadi dan harusdicegah dengan cara memberikan pembatasan umur, pembatasan umur merupakan hal yang penting karena ia menjadi salah satu faktor yang mendukung tercapainya tujuan dari perkawinan yaitu membangun keluarga sakinah mawaddah warahmah.Kata Kunci: Korelasi Pembatasan Umur; Perkawinan.